Caterpillars Cooperate to Overcome Plant Glandular Trichome Defenses - Despland, Emma (Frontiers in Ecology and Evolution, 2019)
One common advantage proposed for group-living in animals is social facilitation of feeding, by which food acquisition by an individual is made easier by feeding neighbours. The present paper provides an explanation of social facilitation of feeding in a gregarious leaf-chewing insect, demonstrating how caterpillars cooperate to overwhelm plant trichome defenses and pierce a hole in the leaf on which they feed collectively. Specifically, it tests the hypotheses that the caterpillars feed collectively, that the glandular trichomes of Solanum acerifolium are effective defenses against the specialist caterpillar Mechanitis menapis, and that feeding by early-instar M. menapis is socially facilitated in the presence of glandular trichomes. A field survey showed that Mechanitis menapis on trichome–bearing plants feed collectively on the abaxial surface of leaves during the first larval instars. In a lab experiment comparing feeding on control and ethanol-washed leaves, caterpillars on the glandular-trichome-free washed sides of leaves initiated feeding sooner and had higher survival rates, suggesting that glandular trichomes are effective defenses. Behavioural observations showed that feeding is socially facilitated in response to glandular trichomes: caterpillars on the washed sides of leaves were more likely to begin feeding alone and initiated more separate feeding sites, suggesting that caterpillars are less able to initiate feeding independently in the presence of glandular trichomes. These results demonstrate a novel mechanism of cooperation among folivores, showing how they can benefit from grouping to tackle food sources that would be unavailable to isolated individuals. This study thus demonstrates that social facilitation of feeding extends to insect folivores, a hyper-diverse and abundant feeding guild.